Power Relations between Shadow Government and Society in Mundzir Qabbani's Hukumatu Dzil Novel - Ahfa Rahman Syah; Ismah Nurul Aminah (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This research is supposed to analyze power relations in the Hukumatu Dzil novel by Mundzir Qabbani. This research used the descriptive analysis method that has the purpose of understanding the phenomenon which is experienced by the subject of the research. This research is based on Michel Foucault's theory of power relations and Alain Viala's theory of sequences. Sequencing analysis shows that the power relation between the shadow government to the community is the most dominant issue in the novel. The result shows that practices of power relations in the novel matched Foucault's theory that power is not only carried out through repressive (violence or threats) but can also use in a non-repressive way. Power relations between the shadow government and society occurred through minds and bodies. Power relations through minds occur by manipulation and stigmatization, which are spread through religion, culture, state, and institutions. Meanwhile, power relations through the body occurred by manipulating the social body. The power relations shown by the community against the shadow government are carried out by manipulation through religious media.